PERAN PANITERA PENGGANTI DALAM PELAKSANAAN ASAS PERADILAN YANG CEPAT, SEDERHANA BIAYA RINGAN: Studi di Pengadilan Negeri Padang Kelas IA - Yetti, Arni (UNES Journal of Swara Justisia, 2020)
The role of the substitute clerk in the implementation of the judicial principle that is fast, simple and inexpensive, as referred to in Article 45 of the Regulation of the Supreme Court of the Republic of Indonesia No. 7 of 2015 concerning the Organization and Work Procedure of the Registrar and Secretariat of the Court. The role of the criminal justice bureaucracy in the courts is very important to realize substantial justice because the Criminal Procedure Code adheres to a service model in the administration of criminal justice. The Substitute Registrar in the implementation of fast, simple, low-cost judicial principles at the Padang Class IA District Court is very decisive in the trial process to produce a quality decision to fulfill a sense of justice for the parties involved. The principle of a simple, fast and low-cost judicial system is one of the principles in the justice system in Indonesia as regulated in Article 4 Paragraph (2) of Law No. 48 of 2009 concerning Judicial Authority which reads "The court helps justice seekers and tries to overcome all obstacles and obstacles to achieve justice. simple, fast, and low-cost justice can be achieved". The role of the substitute clerk in the implementation of fast, simple, low-cost judicial principles at the Padang Class IA District Court is in charge of preparing the trial before the trial, during the trial and or the trial is in progress and after the trial and post-trial, such as assisting the judge in the trial, recording the course of the trial. then put it in the minutes of the trial. The obstacles encountered by the substitute clerk in the implementation of the principle of justice are fast, simple, low cost at the Padang Class IA District Court, both internally and externally. Internal factors, namely: a) The large number of incoming cases, making it difficult to determine the day of the trial; b) The existence of one of the Panel of Judges who handles criminal cases who are sick, on leave or are carrying out other tasks outside the city, thus causing disruption of the trial agenda that has been previously determined. External factors, namely: a) The presence of witnesses who are not on time from the trial agenda that has been set; b) The condition of the defendant who is sick, which is confirmed by a doctor's statement; c) The Public Prosecutor cannot present witnesses for several trials; e) The defendant or victim is unable to present a witness, because the witness is domiciled outside the city of Padang.